Elevated Seminal Plasma TLR-2 Levels are Associated with Leukocytospermia - Rehab Sh. Al-Maliki (Dubai Medical Journal)
Introduction: Leukocytospermia is associated with male infertility, but its underlying mechanisms are not fully understood. This study aimed to investigate the association between seminal plasma toll-like receptor 2 (TLR-2) and prostaglandin E2 (PGE2) levels and leukocytospermia in infertile Iraqi men, and to evaluate their potential as differential biomarkers.